PENDAMPINGAN TATA KELOLA DAN MANAJEMEN PADA KEGIATAN ABDIMAS MASJID - Sriyono, Sriyono; Sari, Dewi Komala; Febriansah, Rizky Eka; Prapanca, Detak (UNIVERSITAS PGRI MADIUN, 2019)
Abstract. The objective in this Abdimas is to provide governance assistance and the implementation of management functions at each mosque activity. The implementation method is to choose partners who have problems with the management and implementation of mosque management, being our initial partner is the Salahuddin mosque which is in the Puri Suryajaya residential complex area of Sidoarjo, while the second partner of this abimas is the Sido Nur An Nur mosque. This partner was chosen because the Salahudin mosque and An Nur Sidoarjo mosque had problems both in the governance of the mosque and in its financial management. In addition, the two mosques are quite active in organizing religious activities and relatively large amounts of funds are collected, but the difficulties in managing them. We strive to overcome the problem by offering several solutions as follows: (1) Developing professional organizational structures and clear Job Disks in the mosque organization. (2) Making a strategic plan for activities for mosques in the future (3) Making SOPs for each type of activity. Output targets for this activity are (1) Creation of good mosque governance and organizational structure and Job Desk (2) Creation of clear SOP activities (3) Creation of Strategic Plan for mosque activities within the next 5 years. In the next stage the workshop or training followed by 10 mosques was attended by the chairman of takmir and treasurer of the mosque. Providing assistance and guidance in the field until the partners are truly able to carry out administrative and financial reporting activities.Abstrak. Tujuan dalam Abdimas ini adalah melakukan pendampingan Tata Kelola dan pelaksanaan fungsi-fungsi manajemen pada setiap kegiatan masjid. Metode pelaksanaanya adalah memilih mitra yang mempunyai masalah terhadap tata kelola dan pelaksanaan manajemen masjid, menjadi mitra awal kami adalah masjid Salahuddin yang berada di kawasan komplek perumahan Puri Suryajaya Sidoarjo, sedangkan mitra ke-2 dari abimas ini adalah masjid An Nur Sidoarjo. Dipilihnya mitra ini karena masjid Salahudin dan masjid An Nur Sidoarjo mempunyai masalah baik dalam tata kelola masjidnya maupun dalam pengelolaan keuangannya. Selain itu kedua masjid ini cukup aktif dalam menyelenggarakan kegiatan keagamaan dan dari kegiatan tersebut terhimpun dana yang relatif besar, namun kesulitan dalam pengelolaannya. Kami berusaha untuk mengatasi permasalahan dengan menawarkan beberapa solusi sebagai berikut: (1) Menyusun Struktur Organisasi yang professional serta Job Disk yang jelas pada organisasi masjid tersebut. (2) Membuatkan Rencana Strategis kegiatan untuk masjid di masa depan (3) Membuatkan SOP untuk setiap jenis kegiatan. Target luaran kegiatan ini adalah (1)Terciptanya tata kelola masjid yang baik beserta struktur organisasi dan Job Desk (2)Terciptanya SOP kegiatan yang jelas (3) Terciptanya Renstra kegiatan Masjid dalam waktu 5 tahun ke depan. Pada tahap berikutnya workshop atau pelatihan yang diikuti oleh 10 masjid masing-masing dihadiri oleh ketua takmir dan bendahara masjid. Melakukan pendampingan serta pembinaan dilapangan sampai mitra benar-benar mampu melaksanakan kegiatan administrasi dan pelaporan keuangan.